2015
DOI: 10.1021/acs.joc.5b02024
|View full text |Cite
|
Sign up to set email alerts
|

Copper- and Silver-Catalyzed Diastereo- and Enantioselective Conjugate Addition Reaction of 1-Pyrroline Esters to Nitroalkenes: Diastereoselectivity Switch by Chiral Metal Complexes

Abstract: syn-Diastereoselective conjugate addition of 1-pyrroline esters to nitroalkenes in good yields with an excellent enantioselectivity by using CuOAc/Me-FcPHOX catalyst in the presence of pyridine. In contrast, AgOAc/tBu-ThioClickFerrophos catalyzed the anti diastereoselective conjugate addition with a high enantioselectivity without additional base. Thus, the preparation of chiral 1-pyrroline derivatives bearing diverse stereochemistry could be achieved. The diastereoselective reduction of the imine group in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Fukuzawa and co-workers reported the diastereodivergent CA of 1-pyrroline esters respectively (Scheme 111). 307 In the case of CuOAc and (S,S P )-FcPHOX 308 syn-310 adducts were obtained in high de and excellent ee, whereas using AgOAc and (R,Sp)-ThioClickFerrophos 309 as catalyst, products anti-310 were formed in excellent de and high ee. From the DFT calculations the TS 310A and 310B have been proposed to explain the observed diastereo-and enantioselectivity.…”
Section: Addition To Alkenesmentioning
confidence: 98%
“…Fukuzawa and co-workers reported the diastereodivergent CA of 1-pyrroline esters respectively (Scheme 111). 307 In the case of CuOAc and (S,S P )-FcPHOX 308 syn-310 adducts were obtained in high de and excellent ee, whereas using AgOAc and (R,Sp)-ThioClickFerrophos 309 as catalyst, products anti-310 were formed in excellent de and high ee. From the DFT calculations the TS 310A and 310B have been proposed to explain the observed diastereo-and enantioselectivity.…”
Section: Addition To Alkenesmentioning
confidence: 98%
“…The complementary syn ‐ 193 diastereomer was realized with the N,O‐ligand 194 together with the Cu(II) catalyst, again with high levels of stereoselectivities (up to 99:1 dr and 98% ee ) (Scheme ) . Fukuzawa and co‐workers instead used the same type of ligands 195 or 196 together with either AgOAc or CuOAc to obtain the diastereomeric products anti ‐ 193 and the products ent ‐ syn ‐ 193 (the enantiomers of syn ‐ 193 ) in good to excellent dr and ee values, respectively (Scheme ) . It should be pointed out that the syn and anti designations for diastereomeric products were totally opposite in these two papers, and here we followed Deng's convention for convenience.…”
Section: Metal Complex‐catalyzed Diastereodivergent Reactionsmentioning
confidence: 99%
“…Interestingly, the generation of N -metalated AYs in the presence of chiral ligands has allowed the enantioselective synthesis of pyrrolidines. , In 1991, Grigg and co-workers demonstrated, for the first time, that the addition of a stoichiometric amount of chiral cobalt or manganese complexes with ephedrine derivatives as the chiral ligand in the generation of AYs derived from imines of glycine alkyl esters could give pyrrolidines with up to 96% ee. It was also reported that silver­(I) salts in combination with chiral phosphane ligands can catalyze the 32CA reaction of AYs.…”
Section: Introductionmentioning
confidence: 99%
“…Different metals, such as Zn, , Ag, ,,,, and Cu, , ,,, and chiral ligands, such as 7 , 8 , ,,,,,, or 9 , ,, have been used in the 32CA reactions of N -metalated AYs with electrophilic ethylene derivatives, improving diastereo- and enantioselectivities. Interestingly, while stereoselectivities have been found to be dependent on the chiral ligands, the substitution of the electrophilic ethylene and even the nature of the metal, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation